2017
DOI: 10.1093/jnen/nlx038
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Deregulation of Protein Turnover Pathways in Atm-Deficient Mouse Cerebellum: An Organotypic Study

Abstract: Interferon-stimulated gene 15 (ISG15), an antagonist of the ubiquitin pathway, is elevated in cells and brain tissues obtained from ataxia telangiectasia (A-T) patients. Previous studies reveal that an elevated ISG15 pathway inhibits ubiquitin-dependent protein degradation, leading to activation of basal autophagy as a compensatory mechanism for protein turnover in A-T cells. Also, genotoxic stress (ultraviolet [UV] radiation) deregulates autophagy and induces aberrant degradation of ubiquitylated proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Empirical evidence from our lab has revealed that ISGylation predominantly antagonizes the canonical ubiquitin pathway in cancer (10) and ataxia telangiectasia (A-T) (11), a rare neurodegenerative disease. Since polyubiquitylation of cellular proteins is a prerequisite for protein turnover via the 26S proteasome, and ubiquitin-mediated protein turnover is crucial in maintaining cellular homeostasis, ISG15 proteinopathy (ISG15-mediated defective protein turnover) is proposed to be an underlying cause of malignancy (10,12) and A-T neurodegeneration (11,13) in human and mouse experimental disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence from our lab has revealed that ISGylation predominantly antagonizes the canonical ubiquitin pathway in cancer (10) and ataxia telangiectasia (A-T) (11), a rare neurodegenerative disease. Since polyubiquitylation of cellular proteins is a prerequisite for protein turnover via the 26S proteasome, and ubiquitin-mediated protein turnover is crucial in maintaining cellular homeostasis, ISG15 proteinopathy (ISG15-mediated defective protein turnover) is proposed to be an underlying cause of malignancy (10,12) and A-T neurodegeneration (11,13) in human and mouse experimental disease models.…”
Section: Introductionmentioning
confidence: 99%
“…ISG15, a ubiquitin-like modifier that inhibits polyubiquitination and is involved in a post-translational modification process called ISGylation, has a role in autophagy by conjugating with other proteins to control clearance of protein aggregates 14 . Activation of ISIG15 occurs after cell stress 15 , when neuronal damage is present [16][17][18] , and is hypothesized to be a potential cause of defective mitophagy in neurodegenerative diseases 19 . ISG15 and ISGylation are implicated in the control of mitochondrial OXPHOS and recycling in bone marrow-derived macrophages 20 .…”
mentioning
confidence: 99%
“…ISG15 is elevated in human A-T cells and mice. 26,122 Similarly, interferon signaling is also elevated in mutant SOD1 mice, 93,123 and specifically upregulated in their Figure 1. A proposed model for defective mitophagy in neurodegenerative diseases.…”
Section: Isg15 a Potential Modulator Of Mitophagy In Neurodegeneratimentioning
confidence: 93%